Annual Plan Progress Report 1966-67 - Planning Commission (Planning Commission, 1966)
1966-67 was another difficult year for the Indian economy. The monsoon failed for the second year in succession, and a large part of the country suffered from want of timely and adequate rainfall. As a result agricultural production stagnated around the previous year's level which was itself 16 per cent lower than in 1964-65. Shortage of foodgrains and agricultural raw materials persisted and large imports had to be made to maintain availability even at a very much reduced level- Growth of industrial production further slackened and national income in real terms registered only a marginal increase. Exports fell and the strain on the balance of payments remained unabated. Credit policy continued to be restrictive.
Planning Commission Government of India
Planning Commission Government of India